Bibliotheca symbolica ecclesiæ universalis: the creeds of Christendom, with a history and critical notes / by Philip Schaff - Schaff, Philip (Harper, 1881)
v. 1. The history of creeds.--v. 2. The Greek and Latin creeds, with translations.--v. 3. The evangelical Protestant creeds, with translations.